2021
DOI: 10.1021/acsabm.0c01626
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Diisobutylene Maleic Acid Copolymer (DIBMA) and Its Lipid Particle as a “Stealth” Membrane-Mimetic for Membrane Protein Research

Abstract: The study of membrane proteins remains challenging, especially in a native membrane environment. Recently, major progress has been made using maleic acid copolymers, such as styrene maleic acid, to purify membrane proteins and study them directly with native lipids associated with the membrane. Additional maleic acid copolymers, such as diisobutylene maleic acid (DIBMA) membrane-mimetic systems, are being developed and found to have improved spectroscopic properties and pH stability. We studied DIBMA and its l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…The overall disc-shaped morphology of mature lipodiscs regardless of the type of copolymer used for their preparation has been confirmed by a number of experimental techniques, including electron microscopy, atomic force microscopy [ 90 , 91 ], and small-angle scattering [ 67 , 92 ] techniques, and computer simulations [ 8 , 93 , 94 ] (see Figure 3 ). Both experiments and computer simulations indicate that the lipid patch is wrapped in a single layer [ 3 ] of polymer similar to nucleic acids in the histone complex or membrane-scaffolding protein in nanodiscs.…”
Section: Formation Structure and Dynamics Of Lipodiscsmentioning
confidence: 88%
“…The overall disc-shaped morphology of mature lipodiscs regardless of the type of copolymer used for their preparation has been confirmed by a number of experimental techniques, including electron microscopy, atomic force microscopy [ 90 , 91 ], and small-angle scattering [ 67 , 92 ] techniques, and computer simulations [ 8 , 93 , 94 ] (see Figure 3 ). Both experiments and computer simulations indicate that the lipid patch is wrapped in a single layer [ 3 ] of polymer similar to nucleic acids in the histone complex or membrane-scaffolding protein in nanodiscs.…”
Section: Formation Structure and Dynamics Of Lipodiscsmentioning
confidence: 88%
“…Recent studies have demonstrated the nanodisc formation by a variety of polymers that are cationic, anionic, , zwitterionic, styrene-containing, styrene-free, ,, charge-free, and metal-chelators . Some of these polymers have been shown to be stable against pH, and some of them can be used to form nanodiscs for certain pH values. ,,, This library of amphipathic polymers has significantly expanded the applications of nanodiscs. …”
mentioning
confidence: 99%
“…Lipodisq nanoparticles or SMALPs can maintain the structural and functional integrity of membrane proteins which is very difficult for traditional membrane systems. , Lipodisq nanoparticles can provide better quality experimental data for various biophysical techniques such as NMR and EPR for studying the structural dynamics of integral membrane proteins. Several forms of SMA copolymers are available in varying sizes and ratios of styrene to maleic acids to solubilize membrane proteins. ,, Various forms of reversible addition–fragmentation chain transfer (RAFT)-synthesized SMA polymers and di-isobutylene maleic acid (DIBMA) copolymers are also available to solubilize membrane proteins. Figure shows an illustrative example of KCNQ1 incorporated into different membrane environments. The dynamic motion of integral membrane proteins is higher in detergent micelles, while the dynamic motion is restricted in liposomes when compared to that in micelles and this motion is further restricted in nanodiscs or lipodisq nanoparticles. , …”
Section: Current Advances In Membrane Mimetic Systems For Studying In...mentioning
confidence: 99%